Patriotism Values as Portrayed in Selected Poetry of Tennyson's Ulysses and Kaimuddin's Bula Malino : A Comparative Study - Hilmawati; Fathu Rahman; Herawaty Abbas (Hasanuddin University, 2021)
Culture and literature differences raising birth of the uniqueness in every country that enriches the lives of the world community, including Butonese and English. This study aimed to compare patriotism values between the Selected Poetry of Tennyson‘s